A Cuneiform Anthology of Religious Texts from Ugarit. Autographed Texts and Glossaries - de Moor, Johannes C. (1987)
Myth - Myth and Ritual - Ritual - Incantation - Legend. Conversion Table KTU-CARTU. Alphabetic Glossary. Semantic Glossary